Mengenalkan Warna Melalui Model Pembelajaran Picture and Picture Pada Anak Usia Dini - Kamtini Kamtini; Salsabila Hasiana Tanjung; Eva Eriani (Mitra Ash-Shibyan: Jurnal Pendidikan dan Konseling, 2021)
Cognitive abilities include various things, one of which is the ability to recognize colors. However, the ability to recognize colors is less often ruled out by educators and parents. This can be seen from learning that pays more attention to early reading and arithmetic skills. In fact, the ability to recognize colors is a very important aspect of children's brain development. This research was conducted in order to see the role of picture and picture learning in stimulating children to recognize colors. This research is quantitative research using a quasi-experimental method with one group time-series test. The data obtained were analyzed using a regression test to see the effect of the treatment given. The results showed a significance value of 0.00 which was smaller than 0.05, which means the picture and picture learning model has a significant effect on the ability to recognize colors in early childhood.